Análisis y evaluación de los deudores comerciales y otras cuentas por cobrar y su impacto en los resultados financieros de la empresa electrica regional del sur s.a. eerssa, año 2019-2020, propuesta alternativa - Arévalo Castro, Lucia Soledad (2022)
This research thesis work called "Analysis and Evaluation of Trade Debtors and Other Accounts Receivable and its impact on the Financial Results of Southern Regional Electric Company S.A. EERSSA, year 2019-2020, Alternative Proposal”, was developed in compliance with the general objective, the Analysis and evaluation of the item TRADE DEBTORS AND OTHER ACCOUNTS RECEIVABLE, in order to determine the IMPACT ON THE FINANCIAL RESULTS OF EERSSA, YEAR 2019 -2020 through a diagnosis of the overdue portfolio, the application of financial indicators established by the Superintendence of Companies, Securities and Insurance and establishing an alternative proposal, for which it was necessary to apply the specific objectives: The first specific objective allowed a diagnosis to the past due portfolio of consumer accounts receivable from the Electric Company for the period 2019-2020, it was shown that during the year 2019 its past due to portfolio was USD 307,409.37 and for the year 2020 its value is USD 1,900,240.21, with a significant increase of USD 1,592,830.84, because of the COVID 19 Health Emergency, the second objective allowed through financial indicators eros and analysis of the financial statements through the horizontal and vertical method to know the real financial - economic situation of the EERSSA, where it was evidenced that its assets in the account of the Trade Debtors Item and other accounts receivable, record the corporate purpose of The Company is the Sale of Electric Power, with the application of these objectives it was possible to propose an alternative proposal for the recovery of the portfolio and the item trade debtors and other accounts receivable that in 2020 registered an increase in the item accounts receivable Consumers, of the horizontal analysis there was an increase compared to the year 2019, with a relative variation of 135.56%.